Implementasi Gerakan Literasi Sekolah pada Tahap Pembiasaan di SDN Kolor II - Fajariyah, Novi Nurul; Tanjung Sari, Tita; Andiriyanto, Ach (IJPSE Indonesian Journal of Primary Science Education, 2025)
The School Literacy Movement (Gerakan Literasi Sekolah) is a program developed by the Ministry of Education and Culture since 2016. One of the schools in Sumenep Regency that has implemented the GLS is SDN Kolor II, which was selected as the first cohort of PSP (Progran Sekolah Penggerak) in Sumenep. This research aims to examine the implementation of GLS at the habituation stage in SDN Kolor II, focusing specifically on classes IV A and IV B. This study employs a qualitative approach with a case study design, following the research procedures outlined by Creswell. Data collection techniques include interviews, observations, and documentation. The data analysis technique used in this study is based on the Miles & Huberman model. The research involves the school principal, two fourth-grade teachers, and representatives from four fourth-grade students as informants. The results indicate that SDN Kolor II has successfully implemented GLS at the habituation stage through activities that include: 1) Singing the Indonesian national anthem and selected songs. 2) Reading storybooks. 3) Writing compositions. 4) "Adu Cerdas" (Smart Competition). 5) "Sabtu Ekspresi" (Expression Saturday). 6) Organizing a literacy-rich environment. Therefore, it can be concluded that SDN Kolor II, particularly in the fourth grade, has effectively implemented GLS at the habituation stage.